Ethical Considerations In Qualitative Research - Mirza, Hadjer; Mirza, Chahrazed; Bellalem, Fouzi (جامعة الوادي - University of Eloued, 2023)
Abstract: This paper sheds light on ethical considerations that must be taken into account when conducting qualitative research. Ethics revolve around the responsibilities of researchers towards their participants, their audience, their society, and their academic communities. Researchers should refer to some ethical guidelines to ensure they have adhered to the principles of good research practices. This paper summarises the ethical considerations that we generally need to promote in qualitative research when collecting and analysing data. These include ethics of respect and conflict of interest, relationship with participants, Informed consent, confidentiality, anonymity, reporting back to the participants, trustworthiness of research, and issues of translation
Summary Guidelines For Novice Social Science Researchers
مقال
Keywords: Ethics ; Qualitive Research ; Social Sciences ; Researchers